2016
DOI: 10.1021/acs.jpcb.6b06863
|View full text |Cite
|
Sign up to set email alerts
|

Volume of Hsp90 Protein–Ligand Binding Determined by Fluorescent Pressure Shift Assay, Densitometry, and NMR

Abstract: Human heat shock protein 90 (Hsp90) is a key player in the homeostasis of the proteome and plays a role in numerous diseases, such as cancer. For the design of Hsp90 ATPase activity inhibitors, it is important to understand the relationship between an inhibitor structure and its inhibition potential. The volume of inhibitor binding is one of the most important such parameters that are rarely being studied. Here, the volumes of binding of several ligands to recombinant Hsp90 were obtained by three independent e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 42 publications
(75 reference statements)
1
20
0
Order By: Relevance
“…There are several techniques that are capable of determining the volume of protein–ligand binding: the fluorescent pressure shift assay (PressureFluor, FPSA) (Toleikis et al ., 2011, 2016; Skvarnavičius et al ., 2017), vibrating tube densitometry(Barbosa et al ., 2003; Son et al ., 2012; Toleikis et al ., 2016), and the high-pressure NMR (Wilton et al ., 2009; Roche et al ., 2012; Toleikis et al ., 2016). They can determine the change of system volume and compressibility caused by the bound ligand.…”
Section: Assays To Determine Small Molecule Inhibitor Interaction Witmentioning
confidence: 99%
“…There are several techniques that are capable of determining the volume of protein–ligand binding: the fluorescent pressure shift assay (PressureFluor, FPSA) (Toleikis et al ., 2011, 2016; Skvarnavičius et al ., 2017), vibrating tube densitometry(Barbosa et al ., 2003; Son et al ., 2012; Toleikis et al ., 2016), and the high-pressure NMR (Wilton et al ., 2009; Roche et al ., 2012; Toleikis et al ., 2016). They can determine the change of system volume and compressibility caused by the bound ligand.…”
Section: Assays To Determine Small Molecule Inhibitor Interaction Witmentioning
confidence: 99%
“…In this sense, multiple authors have suggested continuing studies of ivermectin and its interactions with the various targets of SARS-CoV-2 in order to use it as a model to guide efforts towards the development of new compounds and treatment strategies ( Tang and Dill, 1998 , Tang and Kaneko, 2020 , Toleikis et al, 2016 ) as has already been done ( Rabie, 2021 ). In fact, ivermectin is currently being investigated in the UK as part of the Platform Randomized Trial of Treatments in the Community for Epidemic and Pandemic Illnesses (PRINCIPLE), the world's largest clinical trial of possible COVID-19 treatments for recovery at home and in other non-hospital settings.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we used two compounds that have a primary sulfonamide group in their structures (Figure 2) and exhibit sub-millimolar binding affinities for CA I and CA II. 40,51 Twodimensional 1 H− 15 N HSQC NMR spectra showed that both 29,32 W denotes water molecules that the protein (P) and ligand (L) release into bulk water after their partial dehydration upon binding. isoforms of carbonic anhydrase are in the slow exchange (in NMR time-scale) between two protein statesthe ligandbound and ligand-freefor compounds 1 and 2.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…These results were compatible with previous findings showing correlations between protein−ligand binding volumes and affinities. 29 To the best of our knowledge, no other values of ΔV b for the family of carbonic anhydrases were reported in the literature. Other globular protein and ligand systems showed rather similar values of ΔV b.…”
Section: ■ Discussionmentioning
confidence: 96%
See 1 more Smart Citation